Carrier core material
The carrier core material, with a specific ferrite composition and inclusion of Ca and Nb, addresses the issues of developing memory and uneven image density in electrophotographic development, achieving stable and high-quality image formation.
Patent Information
- Application Number
- JP2021125260
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-07-30
AI Technical Summary
Existing carrier core materials for electrophotographic development suffer from 'developing memory' and uneven image density due to high electrical resistance and reduced flowability, particularly when Sr is added to the carrier core material.
A carrier core material composed of ferrite particles with a specific compositional formula (MnO)x(MgO)y(Fe2O3)z, where x is between 30mol% and 55mol%, y is greater than 0mol%, and z is between 40mol% and 60mol%, and containing Ca and Nb in specific ranges (0.1mol% to 1.5mol%) to enhance surface irregularity and reduce residual magnetization.
The proposed carrier core material effectively suppresses developing memory and uneven image density, ensuring stable and high-quality image formation even during long-term use.
Smart Images

Figure 0007664787000002 
Figure 0007664787000003 
Figure 0007664787000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a carrier core material, and a carrier for electrophotographic development and a developer for electrophotography each using the same. [Background technology]
[0002] For example, in image forming devices using electrophotography such as facsimiles, printers, and copiers, a toner is attached to an electrostatic latent image formed on the surface of a photoconductor to make it visible, and this visible image is transferred to paper or the like, and then fixed by applying heat and pressure. From the viewpoint of achieving high image quality and colorization, so-called two-component developers containing a carrier and a toner are widely used as developers.
[0003] In a development method using a two-component developer, the carrier and toner are mixed and stirred in a development device, and the toner is charged to a predetermined amount by friction. The developer is then supplied to a rotating development roller, a magnetic brush is formed on the development roller, and the toner is electrically transferred to a photoconductor via the magnetic brush, thereby visualizing the electrostatic latent image on the photoconductor. After the toner is transferred, the carrier is peeled off from the development roller and mixed with the toner again in the development device. For this reason, the carrier is required to have magnetic properties that form a magnetic brush, charging properties that impart a desired charge to the toner, and durability for repeated use.
[0004] Such carriers are generally made of magnetic particles (carrier core materials) such as magnetite and various ferrites, the surfaces of which are coated with resin. However, when a resin-coated carrier, in which the surface of a carrier core material is coated with resin, is mixed with a toner to form a two-component developer, a problem called "development memory" can occur, in which the image density decreases due to the influence of the image from the previous rotation of the developing roller.
[0005] This development memory is believed to be caused by the high electrical resistance of the resin-coated carrier, and as one of the countermeasures, for example, Patent Document 1 proposes a technology in which the shape of the carrier core material is specified and a specified ratio of the carrier core material is exposed from the surface of the resin-coated carrier to suppress the development memory. Patent Document 2 also proposes a technology in which Sr (strontium) is incorporated to form minute irregularities on the surface of the carrier core material particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2010-256759 A [Patent Document 2] JP 2012-159642 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, when Sr is added to the carrier core, the composition SrFe 12 O 19 The oxides precipitate. Since the oxides have high residual magnetization and high coercive force, the fluidity of the carrier decreases and the carrier may not be properly separated from the developing roller. Such a decrease in the fluidity of the carrier or the carrier not being properly separated from the developing roller may cause density unevenness in the image.
[0008] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a carrier core material capable of suppressing development memory and also suppressing uneven density of an image.
[0009] Another object of the present invention is to provide a carrier for electrophotography and a developer for electrophotography which are capable of stably forming images of good quality even after long-term use. [Means for solving the problem]
[0010] The carrier core material according to the present invention, which achieves the above object, has the composition formula (MnO) x (MgO) y (Fe2O3) z (However, x: 30 mol% or more and 55 mol% or less, y: Greater than 0mol% The carrier core material is composed of ferrite particles represented by the formula (x, y, z): 20 mol% or less, z: 40 mol% or more and 60 mol% or less, x+y+z=100 mol%), and is characterized in that it contains Ca in the range of 0.1 mol% or more and 1.5 mol% or less, and Nb in the range of 0.1 mol% or more and 1.5 mol% or less.
[0011] In this specification, the Ca and Nb contents are values measured by the method described in the Examples below. In addition, in this specification, the terms "ferrite particles," "carrier core material," "electrophotographic development carrier," and "electrophotographic developer" each mean an aggregate (powders) of individual particles.
[0012] In the carrier core material having the above structure, the Ca / Nb content ratio in mol % of Ca and Nb is preferably 1.0 or more.
[0013] In the carrier core material having the above-mentioned configuration, the maximum peak-to-valley depth Rz on the surface of the ferrite particle is preferably 1.7 μm or more and 2.5 μm or less.
[0014] In the carrier core material having the above-mentioned configuration, the residual magnetization σ r is 1.0(A m 2 / kg) or less.
[0015] In the carrier core material having the above-mentioned configuration, the coercive force H c is 10(A / m×10 3 / (4π)) or less.
[0016] In the carrier core material having the above-mentioned configuration, the pore volume of the ferrite particles measured by mercury intrusion porosimetry is 0.003 cm 3 / g or more 0.02cm 3It is preferable that the molecular weight is not more than 1 / g.
[0017] In addition, in the carrier core material having the above-mentioned configuration, a magnetic field of 79.58×10 3 The magnetization σ of the ferrite particles when A / m (1000 Oersted) is applied 1k 45Am 2 / kg or more 75Am 2 / kg or less is preferable.
[0018] In the carrier core material having the above-mentioned configuration, the volume average particle diameter (hereinafter sometimes referred to as "average particle diameter") D of the ferrite particles 50 It is preferable that the thickness is 20 μm or more and 75 μm or less.
[0019] According to the present invention, there is also provided a carrier for electrophotographic development, characterized in that the surface of any one of the carrier core materials described above is coated with a resin.
[0020] Furthermore, according to the present invention, there is provided an electrophotographic developer comprising the above-described electrophotographic development carrier and a toner.
[0021] In addition, "maximum peak-valley depth Rz" and "residual magnetization σ r ”, “Coercive force H c " 、 "Pore volume", "Magnetization σ 1k ", "Volume average particle size D 50 " is a value measured by the method described in the Examples section below. Effect of the Invention
[0022] The carrier core material according to the present invention can suppress development memory and also suppress uneven density of images.
[0023] Furthermore, by using a developer containing the carrier core material according to the present invention, it is possible to stably form images of good quality even after long-term use. [Brief description of the drawings]
[0024] [Figure 1] 1 is a SEM-EDS photograph (Ca element and Nb element) of a carrier core material of the present invention. [Diagram 2] 1 is a SEM photograph (magnification: 1000 times) of the carrier core material of Example 8. [Diagram 3] 1 is a SEM photograph (magnification: 1000 times) of the carrier core material of Comparative Example 3. [Figure 4] 1 is a schematic diagram showing an example of a developing device using an electrophotographic developer according to the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] As a result of extensive research by the inventors to obtain a carrier core material capable of suppressing development memory and uneven density, they discovered that by incorporating a specified amount of Ca (calcium) and Nb (niobium) in a carrier core material composed of ferrite particles of a specified composition, it is possible to make the surface of the carrier core material uneven and suppress development memory without reducing the fluidity of the carrier or causing poor separation from the developing roller, thereby resulting in the invention.
[0026] That is, one of the major features of the carrier core material according to the present invention is that it contains Ca in the range of 0.1 mol % or more and 1.5 mol % or less, and Nb in the range of 0.1 mol % or more and 1.5 mol % or less.
[0027] When the carrier core material contains only Ca, a crystalline phase of a Ca-Fe-O compound is generated, which can roughen the surface of the carrier core material to some extent, but does not sufficiently suppress the occurrence of development memory. On the other hand, when the carrier core material contains Nb together with Ca, a crystalline phase of a Ca-Nb-O compound is preferentially generated during firing and remains at the grain boundaries of the ferrite particles, suppressing the in-plane growth of the crystals of the ferrite particles and promoting the roughening of the surface of the ferrite particles. In addition, the Ca-Nb-O compound is less likely to increase the residual magnetization and coercive force of the carrier core material than the oxides of Sr and Fe that have been used in the past.
[0028] In addition, it has been confirmed by energy dispersive X-ray spectroscopy (EDS) of the carrier core material produced by a scanning electron microscope (SEM) that a crystal phase of Ca-Nb-O compound is generated during firing when Ca and Nb are mixed as raw material components of the carrier core material. Figure 1 shows an example of an SEM-EDS photograph of a carrier core material. Figure 1(a) is an SEM photograph of the carrier core material, Figure 1(b) is a partially enlarged photograph of Figure 1(a), Figure 1(c) is a photograph showing the presence area of Ca element in the field of view of Figure 1(b), and Figure 1(d) is a photograph showing the presence area of Nb element in the field of view of Figure 1(b). As is clear from a comparison of Figure 1(c) and Figure 1(d), the Ca element and the Nb element are present in almost the same region, and it can be seen that a crystal phase of Ca-Nb-O compound is generated in the carrier core material.
[0029] The respective contents of Ca and Nb are in the range of 0.1 mol% to 1.5 mol%. If the Ca and Nb contents are less than 0.1 mol%, the desired effect of the present invention cannot be obtained. On the other hand, if the Ca and Nb contents exceed 1.5 mol%, the coercive force H c This can lead to an increase in density and cause unevenness in the density.
[0030] In addition, the Ca / Nb content ratio in mol% of Ca and Nb is preferably 1.0 or more. If the Ca / Nb content ratio is less than 1.0, that is, if the Nb content is greater than the Ca content, there will be Nb that does not contribute to the formation of Ca-Nb-O compounds, and although the reason is not yet clear, there is a risk that a part of the ferrite phase will decompose to form a hematite phase, resulting in the occurrence of development memory. The preferred upper limit of the Ca / Nb content ratio is 10.0, and the more preferred upper limit is 5.0.
[0031] The ferrite particles constituting the carrier core material of the present invention are represented by the composition formula (MnO x (MgO) y (Fe2O3) z(wherein x is 30 mol % or more and 55 mol % or less, y is 20 mol % or less, z is 40 mol % or more and 60 mol % or less, and x+y+z=100 mol %). If x exceeds 55 mol % and y exceeds 20 mol %, the magnetization of the carrier core material is too low, and problems such as carrier adhesion may occur in actual use. If x is less than 30 mol %, the magnetization of the carrier core material is too high, and image unevenness may occur.
[0032] The maximum peak-valley depth Rz of the surface of the ferrite particles constituting the carrier core material of the present invention is preferably in the range of 1.7 μm or more and 2.5 μm or less. If the maximum peak-valley depth Rz of the surface of the ferrite particles is less than 1.7 μm, when the surface of the carrier core material is resin-coated to form a resin-coated carrier, the carrier core material cannot be sufficiently exposed on the surface of the resin-coated carrier, and the counter charge accumulated in the resin-coated carrier cannot be smoothly released to the outside, which may cause development memory. On the other hand, if the maximum peak-valley depth Rz of the surface of the ferrite particles exceeds 2.5 μm, the fluidity of the resin-coated carrier may decrease and density unevenness may occur. A more preferable range of the maximum peak-valley depth Rz is in the range of 1.7 μm or more and 2.2 μm or less. The maximum peak-valley depth Rz of the surface of the ferrite particles can be controlled by the amount of Ca and Nb added in the raw material and the firing conditions in the manufacturing process.
[0033] The residual magnetization σ of the ferrite particles constituting the carrier core material of the present invention r is 1.0(A m 2 / kg) or less. r is 1.0(A m 2 If the residual magnetization of the ferrite particles exceeds σ, the carrier may not be properly separated from the developing roller, resulting in uneven density in the image. r A more preferable upper limit of 0.8(A m 2 / kg), and the residual magnetization σ r The preferred lower limit of is 0.5(A m 2 / kg).
[0034] The coercive force H of the ferrite particles constituting the carrier core material of the present invention c is 10(A / m×10 3 / (4π)) or less. c is 10(A / m×10 3 If the magnetic flux density exceeds 4π / (4π), the carrier may not be properly separated from the developing roller, resulting in uneven density in the image. c A more preferable upper limit is 9.5 (A / m×10 3 / (4π)). Also, the coercive force H c The preferred lower limit is 5.0 (A / m×10 3 / (4π)).
[0035] The pore volume of the ferrite particles constituting the carrier core material of the present invention is 0.003 cm 3 / g or more 0.02cm 3 / g or less. The pore volume of the ferrite particles is preferably 0.003 cm 3 If the pore volume of the ferrite particles is less than 0.02 cm3 / g, the magnetization per particle of the carrier core material becomes too large, which may cause a failure in detaching the carrier from the developing roller and result in uneven density in the image. 3 If the pore volume of the ferrite particles exceeds 0.004 cm3 / g, the internal voids become too large, the magnetization per particle of the carrier core material becomes too small, and the carrier is likely to scatter. 3 / g or more 0.015cm 3 / g or less.
[0036] The magnetization σ of the ferrite particles constituting the carrier core material of the present invention 1k is 45Am 2 / kg or more 75Am 2 / kg or less. The magnetization σ of the ferrite particles is preferably 1k 45Am 2 If the magnetization ratio is less than 1 / kg, the magnetic force becomes too small, and there is a risk of the carrier scattering. 1k 75Am 2If the magnetic force exceeds 1000g / kg, the magnetic force becomes too strong, causing the carrier to be poorly separated from the developing roller, resulting in uneven density in the image.
[0037] The average particle diameter D of the ferrite particles constituting the carrier core material of the present invention 50 The particle size is preferably in the range of 20 μm or more and 75 μm or less, and more preferably in the range of 30 μm or more and 40 μm or less. In addition, it is preferable that the particle size distribution of the ferrite particles is sharp.
[0038] Although there is no particular limitation on the method for producing the ferrite particles constituting the carrier core material of the present invention, the production method described below is preferable.
[0039] First, Fe component raw material, Mn component raw material, Mg component raw material, Ca component raw material, Nb component raw material, and additives are weighed out as necessary. As the Fe component raw material, Fe2O3 and the like are preferably used. As the Mn component raw material, MnCO3, Mn3O4, and the like can be used, as the Mg component raw material, MgO, Mg(OH)2, MgCO3, MgFe2O4 can be used, as the Ca component raw material, CaO, Ca(OH)2, CaCO3, and the like can be used, and as the Nb component raw material, Nb2O5, NbO2, Nb2O3, and the like can be used.
[0040] Next, the raw materials are put into a dispersion medium in the same mass ratio as the target carrier core material composition to prepare a slurry. Water is suitable as the dispersion medium used in the present invention. In addition to the above-mentioned pre-baking raw materials, a binder, a dispersant, etc. may be mixed into the dispersion medium as necessary. For example, polyvinyl alcohol can be used as the binder. The amount of the binder to be mixed is preferably about 0.1% by mass to 2% by mass in the slurry. In addition, for example, ammonium polycarboxylate can be used as the dispersant. The amount of the dispersant to be mixed is preferably about 0.1% by mass to 2% by mass in the slurry. In addition, a reducing agent such as carbon black, a pH adjuster such as ammonia, a lubricant, a sintering accelerator, etc. may be mixed. The solid content concentration of the slurry is preferably in the range of 50% by mass to 90% by mass. More preferably, it is 60% by mass to 80% by mass. If it is 60% by mass or more, there are few pores in the particles in the granulated product, and insufficient sintering during firing can be prevented.
[0041] The weighed raw materials may be mixed, calcined, and deagglomerated, and then added to a dispersion medium to prepare a slurry. The calcination temperature is preferably in the range of 750°C to 1000°C. If it is 750°C or higher, partial ferritization by calcination proceeds, the amount of gas generated during calcination is small, and solid-state reactions proceed sufficiently, which is preferable. On the other hand, if it is 1000°C or lower, sintering by calcination is weak, and the raw materials can be sufficiently pulverized in the subsequent slurry pulverization process, which is preferable. In addition, air is preferable as the atmosphere during calcination.
[0042] Next, the slurry prepared as described above is wet-pulverized. For example, wet-pulverization is performed for a predetermined time using a ball mill or a vibration mill. The average particle size of the raw material after pulverization is preferably 5 μm or less, more preferably 1 μm or less. It is preferable that media of a predetermined particle size is contained inside the vibration mill or ball mill. Examples of the media material include iron-based chrome steel and oxide-based zirconia, titania, alumina, etc. The form of the pulverization process may be either continuous or batchwise. The particle size of the pulverized product is adjusted by the pulverization time, rotation speed, material and particle size of the media used, etc.
[0043] The pulverized slurry is then spray-dried to form granules. Specifically, the slurry is introduced into a spray dryer, such as a spray drier, and sprayed into the atmosphere to form spherical granules. The atmospheric temperature during spray drying is preferably in the range of 100°C to 300°C. This results in spherical granules with a particle size of 10 μm to 200 μm. Next, if necessary, the obtained granules are classified using a vibrating sieve to produce granules with a predetermined particle size range.
[0044] Next, the granulated material is put into a furnace heated to a predetermined temperature and sintered by a general method for synthesizing ferrite particles to generate ferrite particles. The sintering temperature is preferably in the range of 1100°C to 1350°C. If the sintering temperature is 1100°C or lower, phase transformation is unlikely to occur and sintering is unlikely to proceed. If the sintering temperature exceeds 1350°C, excessive sintering may cause excessive grains to be generated. The heating rate up to the sintering temperature is preferably in the range of 250°C / h to 500°C / h. The holding time at the sintering temperature is preferably 2 hours or more. The unevenness of the surface of the ferrite particles can also be adjusted by the oxygen concentration in the sintering process. Specifically, the oxygen concentration is set to 500 ppm to 100,000 ppm. Also, the oxidation state of the ferrite phase may be adjusted by setting the oxygen concentration during cooling lower than the oxygen concentration during sintering. Specifically, the oxygen concentration is set to the range of 500 ppm to 30,000 ppm. The oxygen concentration during heating, sintering and cooling is preferably controlled within the range of 500 ppm to 100,000 ppm.
[0045] The sintered product thus obtained is disintegrated as necessary. Specifically, for example, the sintered product is disintegrated by a hammer mill or the like. The disintegration process may be either continuous or batchwise. After the disintegration process, classification may be performed to adjust the particle size to a predetermined range as necessary. As a classification method, a conventionally known method such as wind classification or sieve classification may be used. After primary classification by a wind classifier, the particle size may be adjusted to a predetermined range by a vibrating sieve or ultrasonic sieve. Furthermore, after the classification process, non-magnetic particles may be removed by a magnetic field separator. The average particle size of the ferrite particles is preferably in the range of 20 μm to 75 μm.
[0046] Thereafter, if necessary, the classified ferrite particles may be heated in an oxidizing atmosphere to form an oxide film on the particle surface to increase the resistance of the ferrite particles (resistance-increasing treatment). The oxidizing atmosphere may be either an air atmosphere or a mixed atmosphere of oxygen and nitrogen. The heating temperature is preferably in the range of 200°C to 800°C, more preferably in the range of 360°C to 550°C. The heating time is preferably in the range of 0.5 hours to 5 hours. From the viewpoint of homogenizing the surface and the interior of the ferrite particles, a low heating temperature is desirable.
[0047] The ferrite particles prepared as described above are used as the carrier core material of the present invention. In order to obtain the desired charging properties, the outer periphery of the carrier core material is coated with a resin to form a carrier for electrophotographic development.
[0048] The resin that coats the surface of the carrier core material may be any of the conventionally known resins, such as polyethylene, polypropylene, polyvinyl chloride, poly-4-methylpentene-1, polyvinylidene chloride, ABS (acrylonitrile-butadiene-styrene) resin, polystyrene, (meth)acrylic resins, polyvinyl alcohol resins, as well as thermoplastic elastomers such as polyvinyl chloride, polyurethane, polyester, polyamide, and polybutadiene, and fluorosilicone resins.
[0049] To coat the surface of the carrier core material with a resin, a solution or dispersion of the resin may be applied to the carrier core material. As the solvent for the coating solution, one or more of the following may be used: aromatic hydrocarbon solvents such as toluene and xylene; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; cyclic ether solvents such as tetrahydrofuran and dioxane; alcohol solvents such as ethanol, propanol, and butanol; cellosolve solvents such as ethyl cellosolve and butyl cellosolve; ester solvents such as ethyl acetate and butyl acetate; and amide solvents such as dimethylformamide and dimethylacetamide. The resin component concentration in the coating solution is generally in the range of 0.001% by mass to 30% by mass, particularly 0.001% by mass to 2% by mass.
[0050] The resin can be coated onto the carrier core material by, for example, a spray-drying method, a fluidized bed method, a spray-drying method using a fluidized bed, a dipping method, etc. Among these, the fluidized bed method is particularly preferred because it can be efficiently coated with a small amount of resin. In the case of the fluidized bed method, for example, the amount of resin coating can be adjusted by the amount of resin solution sprayed and the spraying time.
[0051] The particle size of the carrier is generally in the range of 20 μm or more and 75 μm or less, particularly preferably 30 μm or more and 40 μm or less, in terms of volume average particle size.
[0052] The electrophotographic developer according to the present invention is obtained by mixing the carrier and toner prepared as described above. There is no particular limitation on the mixture ratio of the carrier and toner, and it may be appropriately determined based on the development conditions of the developing device to be used. In general, the toner concentration in the developer is preferably in the range of 1% by mass or more and 15% by mass or less. If the toner concentration is less than 1% by mass, the image density becomes too thin, while if the toner concentration exceeds 15% by mass, toner scattering occurs in the developing device, which may cause problems such as dirt inside the device or toner adhesion to the background part of the transfer paper. A more preferable toner concentration is in the range of 3% by mass or more and 10% by mass or less.
[0053] The toner may be produced by a conventional method such as a polymerization method, a pulverization classification method, a melt granulation method, a spray granulation method, etc. Specifically, a toner containing a colorant, a release agent, a charge control agent, etc. in a binder resin mainly composed of a thermoplastic resin can be suitably used.
[0054] Generally, the particle size of the toner is preferably in the range of 5 μm to 15 μm, more preferably 7 μm to 12 μm, in terms of the volume average particle size measured with a Coulter counter.
[0055] If necessary, a modifier may be added to the toner surface. Examples of the modifier include silica, alumina, zinc oxide, titanium oxide, magnesium oxide, polymethyl methacrylate, etc. These may be used alone or in combination of two or more.
[0056] The carrier and toner can be mixed using a conventionally known mixing device, such as a Henschel mixer, a V-type mixer, a tumbler mixer, or a hybridizer.
[0057] Although there is no particular limitation on the developing method using the developer of the present invention, a magnetic brush development method is preferable. Fig. 4 shows a schematic diagram of an example of a developing device that performs magnetic brush development. The developing device shown in Fig. 4 includes a rotatable developing roller 3 incorporating a plurality of magnetic poles, a regulating blade 6 that regulates the amount of developer on the developing roller 3 that is transported to a developing section, two screws 1 and 2 that are arranged in parallel in the horizontal direction and stir and transport the developer in opposite directions, and a partition plate 4 that is formed between the two screws 1 and 2 and allows the developer to move from one screw to the other screw at both ends of the screws and prevents the developer from moving at any other than both ends.
[0058] The two screws 1 and 2 have helical blades 13 and 23 formed on shafts 11 and 21 at the same inclination angle, and are rotated in the same direction by a driving mechanism (not shown) to transport the developer in opposite directions. The developer moves from one screw to the other at both ends of the screws 1 and 2. This causes the developer, which is made up of toner and carrier, to constantly circulate and be stirred inside the device.
[0059] Meanwhile, the developing roller 3 is a metal cylindrical body with a surface roughness of several μm, and has a fixed magnet with five magnetic poles arranged in order as magnetic pole generating means: a developing magnetic pole N1, a transporting magnetic pole S1, a peeling magnetic pole N2, a pumping magnetic pole N3, and a blade magnetic pole S2. When the cylindrical body of the developing roller 3 rotates in the direction of the arrow, the developer is pumped up from the screw 1 to the developing roller 3 by the magnetic force of the pumping magnetic pole N3. The developer carried on the surface of the developing roller 3 is regulated in layer by a regulating blade 6, and then transported to the development area.
[0060] In the development area, a bias voltage in which an AC voltage is superimposed on a DC voltage is applied from a transfer voltage power source 8 to the development roller 3. The DC voltage component of the bias voltage is set to a potential between the background portion potential and the image portion potential on the surface of the photoconductor drum 5. The background portion potential and the image portion potential are set to potentials between the maximum and minimum values of the bias voltage. The peak-to-peak voltage of the bias voltage is preferably in the range of 0.5 kV to 5 kV, and the frequency is preferably in the range of 1 kHz to 10 kHz. The waveform of the bias voltage may be any of a square wave, a sine wave, a triangular wave, and the like. This causes the toner and carrier to vibrate in the development area, and the toner adheres to the electrostatic latent image on the photoconductor drum 5 to develop it.
[0061] The developer on the developing roller 3 is then transported inside the device by the transport magnetic pole S1, peeled off from the developing roller 3 by the peeling electrode N2, and circulated again within the device by the screws 1 and 2, where it is mixed and stirred with the developer not being used for development. Then, new developer is supplied from the screw 1 to the developing roller 3 by the pumping pole N3.
[0062] In the embodiment shown in FIG. 4, the developing roller 3 has five magnetic poles. However, it is of course possible to increase the number of magnetic poles to eight, ten, or twelve in order to increase the amount of developer movement in the development area or to improve the pumping performance, etc. EXAMPLES
[0063] Example 1 As raw materials, 10.0 kg of Fe2O3 (average particle size: 0.6 μm), 3.8 kg of Mn3O4 (average particle size: 3.4 μm), 2.6 kg of MgFe2O4 (average particle size: 3.2 μm), 0.081 kg of CaCO3 (average particle size: 0.6 μm), and 0.095 kg of Nb2O5 (average particle size: 3.5 μm) were dispersed in 5.4 kg of pure water, and 30 g of carbon black was added as a reducing agent, 139 g of polycarboxylate ammonium dispersant as a dispersant, and 5 g of ammonia water (25 wt% aqueous solution) were added to obtain a mixture. This mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. This mixed slurry was sprayed into hot air at about 140° C. using a spray dryer to obtain dried granules with a particle size of 10 μm to 75 μm. Fine particles with a particle size of 25 μm or less were removed from the granules using a sieve. The granulated material was placed in an electric furnace and heated to 1200°C over 4.5 hours. It was then sintered by holding it at 1200°C for 3 hours. The oxygen concentration in the electric furnace was adjusted to 100,000 ppm during the heating stage and 15,000 ppm during the cooling stage. The obtained fired product was disintegrated with a hammer mill and then classified with a vibrating sieve to obtain a carrier core material having an average particle size of 35.7 μm.
[0064] The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0065] Next, the surface of the carrier core material thus obtained was coated with resin to prepare a carrier. Specifically, 450 parts by mass of silicone resin and 9 parts by mass of (2-aminoethyl)aminopropyltrimethoxysilane were dissolved in 450 parts by mass of toluene as a solvent to prepare a coating solution. This coating solution was applied to 50,000 parts by mass of the carrier core material using a fluidized bed type coating device, and heated in an electric furnace at a temperature of 300°C to obtain a carrier. The following examples and comparative examples were also obtained in the same manner.
[0066] The obtained carrier and toner having an average particle size of about 5.0 μm were mixed for a predetermined time using a pot mill to obtain a two-component electrophotographic developer. In this case, the carrier and toner were adjusted so that the mass of the toner / (mass of the toner and carrier)=5 / 100. Developers were obtained in the same manner for all the following examples and comparative examples. The obtained developer was evaluated using an actual machine as described below. The evaluation results are also shown in Table 1.
[0067] Example 2 A carrier core material having an average particle size of 36.2 μm was obtained in the same manner as in Example 1, except that the electric furnace temperature in the firing step was changed to 1240° C. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0068] Example 3 A carrier core material having an average particle size of 36.1 μm was obtained in the same manner as in Example 1, except that the electric furnace temperature in the firing process was changed to 1210°C and the oxygen concentration in the electric furnace was adjusted so that it was 100,000 ppm during the heating stage and 25,000 ppm during the cooling stage. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0069] Example 4 A carrier core material with an average particle diameter of 35.6 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.122 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.143 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0070] Example 5 A carrier core material with an average particle diameter of 35.1 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.163 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.190 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0071] Example 6 A carrier core material with an average particle diameter of 35.2 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.061 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.071 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0072] Example 7 A carrier core material with an average particle diameter of 36.1 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.041 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.048 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0073] Example 8 A carrier core material with an average particle diameter of 35.7 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.081 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.071 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described below. The measurement results are shown in Table 1. Also, an SEM photograph of the carrier core material is shown in Figure 2.
[0074] Example 9 A carrier core material with an average particle diameter of 35.5 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.081 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.047 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0075] Example 10 A carrier core material with an average particle diameter of 35.3 μm was obtained in the same manner as in Example 3, except that the raw materials used were 10.0 kg of Fe2O3 (average particle diameter: 0.6 μm), 3.8 kg of Mn3O4 (average particle diameter: 3.4 μm), 2.6 kg of MgFe2O4 (average particle diameter: 3.2 μm), 0.081 kg of CaCO3 (average particle diameter: 0.6 μm), and 0.024 kg of Nb2O5 (average particle diameter: 3.5 μm). The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0076] Comparative Example 1 As raw materials, 9.5 kg of Fe2O3 (average particle size: 0.6 μm), 4.2 kg of Mn3O4 (average particle size: 2.0 μm), 2.7 kg of MgFe2O4 (average particle size: 3.2 μm), and 0.181 kg of SrCO3 (average particle size: 0.6 μm) were dispersed in 5.4 kg of pure water, and 57 g of carbon black as a reducing agent, 82 g of polycarboxylate ammonium dispersant as a dispersant, and 32 g of hydrochloric acid (35 wt% aqueous solution) were added to make a mixture. This mixture was pulverized using a wet ball mill (media diameter 2 mm) to obtain a mixed slurry. This mixed slurry was sprayed into hot air at about 140° C. using a spray dryer to obtain dried granules with a particle size of 10 μm to 75 μm. Fine particles with a particle size of 25 μm or less were removed from the granules using a sieve. The granulated material was placed in an electric furnace and heated to 1200°C over 4.5 hours. It was then sintered by holding at 1200°C for 3 hours. The oxygen concentration in the electric furnace was adjusted to 10000 ppm during the heating stage and 15000 ppm during the cooling stage. The obtained fired product was disintegrated with a hammer mill and then classified with a vibrating sieve to obtain a carrier core material having an average particle size of 34.9 μm. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0077] Comparative Example 2 Fe2O3 (average particle size: 0.8μm) was weighed out to 50.0mol, and Mn3O4 (average particle size: 2.0μm) was weighed out to 50.0mol in terms of MnO, and pelletized with a roller compactor. The pellets obtained were calcined in a rotary calciner at 850℃ under atmospheric conditions. The pellets were ground in a dry bead mill for 6 hours to obtain a calcined raw material (average particle size: 2.2μm). 16.4kg of the calcined raw material and 0.197kg of SrCO3 (average particle size: 0.6μm) were dispersed in 5.5kg of pure water, and 49g of carbon black was added as a reducing agent and 98g of polycarboxylate ammonium dispersant was added as a dispersant to obtain a mixture. The mixture was ground in a wet ball mill (media diameter 2mm) to obtain a mixed slurry. This mixed slurry was sprayed into hot air at about 140° C. using a spray dryer to obtain dried granules with a particle size of 10 μm to 75 μm. Fine particles with a particle size of 30 μm or less were removed from the granules using a sieve. The granulated material was placed in an electric furnace and heated to 1200° C. over 4.5 hours. It was then sintered by holding at 1200° C. for 3 hours. The oxygen concentration in the electric furnace was adjusted to 15000 ppm. The obtained fired product was disintegrated in a hammer mill and then classified using a vibrating sieve to obtain a fired product with an average particle size of 34.8 μm. Next, the obtained fired product was subjected to an oxidation treatment (resistance increasing treatment) by holding it at 380° C. for 1 hour in an air atmosphere, to obtain a carrier core material. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0078] Comparative Example 3 A carrier core material having an average particle size of 34.3 μm was obtained in the same manner as in Example 3, except that Nb2O5 was not added as a raw material. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described below. The measurement results are shown in Table 1. Also, an SEM photograph of the carrier core material is shown in Figure 3.
[0079] Comparative Example 4 A carrier core material having an average particle size of 35.9 μm was obtained in the same manner as in Example 3, except that CaCO3 was not added as a raw material. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0080] Comparative Example 5 As raw materials, 10.0 kg of Fe2O3 (average particle size: 0.6 μm), 3.8 kg of Mn3O4 (average particle size: 3.4 μm), 2.6 kg of MgFe2O4 (average particle size: 3.2 μm), 0.119 kg of SrCO3 (average particle size: 0.6 μm), and 0.095 kg of Nb2O5 (average particle size: 3.5 μm) were dispersed in 5.4 kg of pure water, and 30 g of carbon black was added as a reducing agent, 139 g of polycarboxylate ammonium dispersant as a dispersant, and 5 g of ammonia water (25 wt% aqueous solution) were added to obtain a mixture. This mixture was pulverized by a wet ball mill (media diameter 2 mm) to obtain a mixed slurry, and a carrier core material with an average particle size of 34.5 μm was obtained in the same manner as in Example 3. The composition, powder characteristics, shape characteristics, magnetic characteristics, etc. of the obtained carrier core material were measured by the methods described later. The measurement results are shown in Table 1.
[0081] (composition analysis) (Fe Analysis) The carrier core material containing iron element was weighed and dissolved in a mixed acid solution of hydrochloric acid and nitric acid. After evaporating this solution to dryness, sulfuric acid water was added to redissolve it and volatilize the excess hydrochloric acid and nitric acid. Solid Al was added to this solution to remove the Fe in the liquid. 3+ All Fe 2+ The Fe in this solution is then reduced to 2+ The amount of ions was quantitatively analyzed by potentiometric titration with potassium permanganate solution, and Fe(Fe 2+ ) was determined. (Mn Analysis) The Mn content of the carrier core material was quantitatively analyzed in accordance with the ferromanganese analysis method (potentiometric titration method) described in JIS G1311-1987. The Mn content of the carrier core material described in this specification is the Mn amount obtained by quantitative analysis using this ferromanganese analysis method (potentiometric titration method). (Analysis of Mg) The Mg content of the carrier core material was analyzed by the following method. The carrier core material was dissolved in an acid solution and quantitatively analyzed by ICP. The Mg content of the carrier core material described in this specification is the amount of Mg obtained by this quantitative analysis using ICP. (Ca analysis) The Ca content of the carrier core material was quantitatively analyzed by ICP in the same manner as in the analysis of Mg. (Nb Analysis) The Nb content of the carrier core material was quantitatively analyzed by ICP in the same manner as in the analysis of Mg. (Sr analysis) The Sr content of the carrier core material was quantitatively analyzed by ICP in the same manner as in the analysis of Mg.
[0082] The composition values (mol %) in Table 1 described later were calculated by the following procedure. From the analytical values of Fe, Mn, and Mg, the molar amounts of Fe2O3, MnO, and MgO were calculated, and the molar ratios (mol%) of Fe2O3, MnO, and MgO were calculated so that the total of Fe2O3, MnO, and MgO was 100 mol%. Next, the molar ratios (mol%) of Ca, Nb, and Sr relative to the total amount (100 mol%) of Fe2O3, MnO, and MgO were calculated.
[0083] (Apparent density AD) The apparent density of the carrier core material was measured in accordance with JIS Z 2504.
[0084] (Flow rate FR) The fluidity of the carrier core material was measured in accordance with JIS Z 2502.
[0085] (Volume average particle size D 50 ) Volume average particle diameter D of carrier core material 50 was measured as the cumulative 50% particle size on a volume basis using a laser diffraction particle size distribution analyzer (Microtrac Model 9320-X100, manufactured by Nikkiso Co., Ltd.).
[0086] (Pore volume) The pore volume was measured as follows. The evaluation device used was a POREMASTER-60GT manufactured by Quantachrome. Specifically, the measurement conditions were: Cell Stem Volume: 0.5 cm 3 , Head pressure: 20PSIA, Surface tension of mercury: 485.00erg / cm 2 , mercury contact angle: 130.00 degrees, high pressure measurement mode: Fixed Rate, motor speed: 1, high pressure measurement range: 20.00 to 10000.00 PSI, 1.200 g of sample was weighed and measured at 0.5 cm 3 The volume B (cm) at 10,000.00 PSI was also measured. 3 / g) to volume A at 100 PSI (cm 3 The value obtained by subtracting the pore volume (1 / g) was taken as the pore volume.
[0087] (Maximum peak / valley depth Rz, average length RSm) The surface was observed with a 100x objective lens using an ultra-deep color 3D shape measuring microscope ("VK-X100" manufactured by Keyence Corporation). Specifically, ferrite particles were first fixed to a flat adhesive tape with a surface, and the measurement field of view was determined with a 100x objective lens, after which the focus was adjusted to the adhesive tape surface using the autofocus function. A laser beam was irradiated from the vertical direction (Z direction) onto the flat adhesive tape surface on which the ferrite particles were fixed, and the surface was scanned in the X and Y directions. In addition, data in the Z direction was obtained by connecting the lens height positions when the intensity of the reflected light from the surface was at its maximum. The position data in the X, Y, and Z directions were connected to obtain the 3D shape of the ferrite particle surface. The auto-photography function was used to capture the 3D shape of the ferrite particle surface. Each parameter was measured using particle roughness inspection software (Mitani Shoji Co., Ltd.). First, as a pretreatment, particle recognition and shape sorting of the three-dimensional shape of the obtained ferrite particle surface were performed. Particle recognition was performed as follows. Of the three-dimensional shape obtained by photography, the maximum value in the Z direction is set to 100%, and the minimum value is set to 0%, and the range between the maximum and minimum values is divided into 100 equal parts. The region corresponding to 100-35% of this was extracted, and the outline of the independent region was recognized as the particle outline. Next, particles that are large, small, or associated were removed by shape selection. This shape selection can reduce errors during the curvature correction that is performed later. Specifically, particles with an area equivalent diameter of 28 μm or less, 38 μm or more, and an acicular ratio of 1.15 or more were removed. Here, the acicular ratio is a parameter calculated from the ratio of the maximum length / diagonal width of the particle, and the diagonal width represents the shortest distance between two straight lines parallel to the maximum length when the particle is sandwiched between them. Next, the portion to be used for analysis was extracted from the three-dimensional surface shape. First, a 15.0 μm square was drawn with the center of gravity determined from the particle outline recognized by the above method as its center. 21 parallel lines were drawn within the square, and 21 roughness curves that fell on those line segments were extracted. Since ferrite particles are almost spherical, the roughness curve extracted has a certain curvature as the background. Therefore, to correct the background, an optimal quadratic curve was fitted and subtracted from the roughness curve. In this case, a low-pass filter was applied with a strength of 1.5 μm, and the cutoff value λ was set to 80 μm. In addition, the average particle diameter of the carrier core material used in the analysis was limited to 32 μm to 34 μm. By limiting the average particle diameter of the carrier core material to be measured to a narrow range in this way, it is possible to reduce errors due to residues that occur during curvature correction.
[0088] The maximum peak-valley depth Rz was calculated as the sum of the highest peak height and the deepest valley depth in the roughness curve. The average value of each parameter for 30 particles was used to calculate the maximum height Rz.
[0089] The average length RSm is calculated by averaging the length of each element, which is defined as a combination of a valley and a peak in the roughness curve. The average value of 30 particles is used to calculate the average length RSm.
[0090] The above-described measurements of the maximum height Rz and average length RSm are performed in accordance with JIS B0601 (2001 edition).
[0091] (Magnetic properties) Using a room temperature dedicated vibrating sample magnetometer (VSM) ("VSM-P7" manufactured by Toei Kogyo Co., Ltd.), the external magnetic field was set to 0 to 79.58 × 10 4 A magnetic field of 79.58×10 A / m (10,000 Oersted) was applied continuously for one cycle. 3 Magnetization σ when A / m (1,000 Oersted) is applied 1k , saturation magnetization σ s , residual magnetization σ r , coercive force H c was measured.
[0092] (bridge resistor) Two 2 mm thick brass plates with electrolytically polished surfaces were used as electrodes, arranged with a distance of 2 mm between the electrodes. 200 mg of carrier core material was then inserted into the gap between the two electrodes, and a 240 mm cross-sectional area was then attached to the back of each electrode. 2 A magnet was placed between the electrodes to form a bridge of the powder to be measured, and a DC voltage of 1000 V was applied between the electrodes, and the current flowing through the carrier core material was measured using the four-terminal method. 2 The electrical resistance of the carrier core material was calculated from the above.
[0093] (Actual machine evaluation) (Development memory) The obtained developer was put into a developing device with the structure shown in Figure 4 (circumferential speed of developing roller Vs: 406 mm / sec, peripheral speed of photosensitive drum Vp: 205 mm / sec, distance between photosensitive drum and developing roller: 0.3 mm), and an initial image was obtained in which solid image areas and non-image areas were adjacent to each other in the circumferential direction of the photosensitive drum, followed by a wide area of intermediate tones. The image density of the area where the solid image of the first rotation of the developing roller was developed on the second rotation of the developing roller and the area where it was not developed was measured using a reflection densitometer (Model TC-6D, manufactured by Tokyo Denshoku Co., Ltd.), and the difference was calculated and evaluated according to the following criteria. The results are shown in Table 2. "◎": Less than 0.003 "○": 0.003 or more and less than 0.006 "△": 0.006 or more and less than 0.020 "×": 0.020 or more
[0094] (Uneven density) The density of five points on each of three evaluation images obtained by the evaluation machine was measured using a reflection densitometer (Model TC-6D, manufactured by Tokyo Denshoku Co., Ltd.) and evaluated according to the following criteria. "Excellent": The maximum difference in density between light and dark areas is less than 0.1, and density unevenness is not visible. "◯": The maximum difference in density between light and dark is 0.1 or more and less than 0.2, and density unevenness is not visible. "Δ": The maximum difference in density is 0.2 or more and less than 0.3, and density unevenness is visible. "X": The maximum difference in density between light and dark areas is 0.3 or more, and density unevenness is visible, making the product unusable.
[0095] [Table 1]
[0096] As is clear from Table 1, in the carrier core materials of Examples 1 to 10 made of MnMg ferrite containing Ca and Nb, the development memory and density unevenness were suppressed to levels that would not cause problems in practical use.
[0097] In contrast, in the carrier core material of Comparative Example 1 made of MnMg ferrite containing Sr, the development memory was suppressed to a level that did not cause problems in practical use, but the unevenness in concentration was visible and was at a level that was problematic in practical use. Also, in the carrier core material of Comparative Example 2 made of Mn ferrite containing Sr, the development memory was suppressed to a level that did not cause problems in practical use, but the unevenness in concentration was visible and was at a level that was problematic in practical use.
[0098] In the carrier core material of Comparative Example 3, which is made of MnMg ferrite containing Ca but not Nb, the unevenness in density was suppressed to a level that does not cause problems in practical use, but the development memory was at a level that poses a problem in practical use.In addition, in the carrier core material of Comparative Example 4, which is made of MnMg ferrite containing Nb but not Ca, the unevenness in density was suppressed to a level that does not cause problems in practical use, but the development memory was at a level that poses a problem in practical use.
[0099] In the carrier core material of Comparative Example 5 constituted by MnMg ferrite containing Nb and Sr, the development memory was suppressed to a non-problematic level, but the density unevenness was at a level that would be problematic in practical use. [Industrial Applicability]
[0100] The carrier core material according to the present invention is useful in that it can suppress development memory and also suppress uneven density of images. [Explanation of symbols]
[0101] 3 Developing roller 5 Photoconductor drum
Claims
1. Composition formula (MnO) x (MgO) y (Fe 2 O 3 ) z (wherein x is 30 mol % or more and 55 mol % or less, y is more than 0 mol % and 20 mol % or less, z is 40 mol % or more and 60 mol % or less, and x + y + z = 100 mol %), Ca is in the range of 0.1 mol% or more and 1.5 mol% or less, Nb is in the range of 0.1 mol% or more and 1.5 mol% or less, A carrier core material comprising:
2. 2. The carrier core material according to claim 1, wherein the Ca / Nb content ratio in mol % of Ca and Nb is 1.0 or more.
3. 3. The carrier core material according to claim 1, wherein the maximum peak-to-valley depth Rz on the surface of the ferrite particle is 1.7 μm or more and 2.5 μm or less.
4. The remanent magnetization σ of the ferrite particles r is 1.0 (A m 2 4. The carrier core material according to claim 1, wherein the molecular weight is 1 / kg or less.
5. The coercive force H of the ferrite particles c is 10 (A / m x 10 3 5. The carrier core material according to claim 1, wherein the n-th order is 0.01 / (4π) or less.
6. The pore volume of the ferrite particles measured by mercury intrusion porosimetry is 0.003 cm 3 / g or more 0.02cm 3 The carrier core material according to any one of claims 1 to 5, wherein the molecular weight is 1 / g or less.
7. Magnetic field 79.58×10 3 The magnetization σ of the ferrite particles when a current of 1000 A / m (1000 Oersted) is applied 1k is 45 Am 2 / kg or more 75Am 2 The carrier core material according to any one of claims 1 to 6, wherein the carrier core material has a density of 1 / kg or less.
8. The volume average particle diameter D of the ferrite particles 50 The carrier core material according to any one of claims 1 to 7, wherein the particle size is 20 µm or more and 75 µm or less.
9. 9. A carrier for electrophotographic development, comprising the carrier core material according to claim 1, the surface of which is coated with a resin.
10. 10. An electrophotographic developer comprising the carrier for electrophotographic development according to claim 9 and a toner.
Citation Information
Patent Citations
Manganese-zinc ferrite magnetic sheet and preparation method thereof
CN110386813A
Hydrothermal synthesis of magnetoplumbite type ferrite
JP1986040823A
Ferrite carrier for electrophotographic development
JP1987297856A
Mn-Zn FERRITE
JP2007031210A
Carrier for electrophotographic developer and developer
JP2008096975A